PERAN KEBIJAKAN PUBLIK DALAM MENGENTASKAN KEMISKINAN DAN KESENJANGAN SOSIAL - Rahmat Salam (GoAcademica Research dan Publishing, 2019)
The research questions that will be investigated are how to establish a clear distinction between poverty and inequality in public policy debates and how public administrators can formulate and implement policies that will reduce world inequality today. Equality is not always seen as an equation of economic conditions but mainly as an equal opportunity to achieve it. This is why it is important to refer to the concept of social justice when addressing inequality. This article will review and analyze the current literature on poverty, inequality and social justice and will suggest some new approaches to eliminating inequality. Although the initiative required to achieve these objectives must come from politics, the public administrator will ultimately be the one to provide a definite plan or procedure to ensure the fulfillment of these political initiatives. This article will discuss how public policymakers can promote equality and social justice.